Tari Kreasi Pramada Yuwati - Ni Made Rahma Chelsia Dewi; I Kt. Suteja; Ni Komang Sri Wahyuni (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2025)
Pramada Yuwati’s dance work was inspired by a book entitled Mahabharata written by Nyoman S. Pendit. In the storyof Dewi Kunti, when she was a teenager, she was given a gift by Rsi Durwasa in the form of a spell, which could bringthe desired god when she recited the spell and at the same time get a child from the god she brought. Out of curiosity,Dewi Kunti wanted to try the spell without thinking about the consequences of pregnancy. The story proves that DewiKunti was negligent from taking responsibility for the consequences of her actions.This phenomenon is rife in theassociation of teenagers today. This prompted the creator to create a creative dance work entitled Pramada Yuwati. Thecreation of Pramada Yuwati's dance works uses the Angripta Sasolahan method (creating dances) which consists ofNgerencana, Nuasen, Makalin, Nelesin, and Ngebah. Ngarencana is the initial process of exploring an idea that iscontemplated intensely. Nuasen means the stage of carrying out a ritual ceremony to ask for the blessing of GodAlmighty so that all processes of creating dance works run smoothly. Makalin, the stage of selecting materials thatsupport the creation of Pramada Yuwati's dance works, such as choosing a place to practice and improvisingmovements. Nelesin is the formation of works by summarizing the results of motion improvisation to produce motionmotifs. Ngebah, the premiere performance of a complete dance work that aims to get an evaluation and make importantchanges in the work. Pramada Yuwati's Creative Dance is a dance work that tells the story of a teenager's negligence,which results in disaster for his life. Using 6 (six) dancers, the semarandhana gamelan as the dance music instrument,and performed on the Natya Mandala Stage, the Indonesian Art Institute, Denpasar.Keywords: Pramada Yuwati, Negligence, Creation